Magnetic resonance imaging for pathobiological assessment and interventional treatment of the coronary arteries. (29th April 2020) - Heidt, Timo; Reiss, Simon; Lottner, Thomas; Özen, Ali C; Bode, Christoph; Bock, Michael; von zur Mühlen, Constantin
Abstract: X-ray-based fluoroscopy is the standard tool for diagnostics and intervention in coronary artery disease. In recent years, computed tomography has emerged as a non-invasive alternative to coronary angiography offering detection of coronary calcification and imaging of the vessel lumen by the use of iodinated contrast agents. Even though currently available invasive or non-invasive techniques can show the degree of vessel stenosis, they are unable to provide information about biofunctional plaque properties, e.g. plaque inflammation. Furthermore, the use of radiation and the necessity of iodinated contrast agents remain unfavourable prerequisites. Magnetic resonance imaging (MRI) is a radiation-free alternative to X-ray which offers anatomical and functional imaging contrasts fostering the idea of non-invasive biofunctional assessment of the coronary vessel wall. In combination with molecular contrast agents that target-specific epitopes of the vessel wall, MRI might reveal unique plaque properties rendering it, for example, 'vulnerable and prone to rupture'. Early detection of these lesions may allow for early or prophylactic treatment even before an adverse coronary event occurs. Besides diagnostic imaging, advances in real-time image acquisition and motion compensation now provide grounds for MRI-guided coronary interventions. In this article, we summarize our research on MRI-based molecular imaging in cardiovascular disease and feature our advances towards real-time MRI-based coronary interventions in a porcine model.